Poziom sprawności a poczucie jakości życia na przykładzie wybranych żołnierzy sił powietrznych = Physical activity level and life quality perception on the example of selected air force soldiers - Jaroszuk, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article was to evaluate the physical fitness of selected air force soldiers from the 31st Tactical Base Air. The study material involved the results of the yearly physical fitness evaluation conducted in 2017. The physical fitness test involves four categories: endurance, upper limbs strength, abdominal muscles strength, as well as speed and agility. The analysis involved 254 persons classified into 8 age groups. The corps included: officers (92), non-commissioned officers (NCOs) (135), and privates (26).
Keywords: sprawność fizyczna; egzamin z sprawności fizycznej; żołnierz zawodowy; physical fitness; physical fitness exams; professional soldier